Bank income and profits over the business and interest rate cycle - Johann Burgstaller (Johannes Kepler University of Linz, Department of Economics, 2006)
If and how the conduct of the banking sector contributes to the propagation of aggregate shocks has become a prominent empirical research question. This study explores what a cyclicality analysis of net interest margins and spreads, as well as profitability figures, can contribute to the discussion. By using time series data for the Austrian banking sector from 1987 to 2005, it is found that many of these measures fall in economic upturns. Net interest income from granting loans and taking deposits from non-banks, however, evolves procyclically and increases with rising interest rates. Combined with the observation that the margins' countercyclical variations are rather small, it can be concluded that there is no striking evidence for a financial accelerator caused by the Austrian banking sector.
Keywords: E32; G21; 330; Bank interest margins; business cycles; financial accelerator; impulse response analysis; Bankgeschäft; Gewinn; Zinsspannenrechnung; Konjunktur; Österreich